Rational Dictators in the Dictator Game Are Seen as Cold and Agentic but Not Intelligent. (August 2022) - Ruessmann, Janna Katrin; Unkelbach, Christian
In Dictator Games, dictators decide how much of a given endowment to send to receivers with no further interactions. We explored the social inferences people draw about dictators from the dictators' money amount sent and vice versa in 11 experiments ( N = 1, 425): Participants rated "unfair" dictators, who sent little or no money, as more agentic, but less communal than "fair" dictators, who sent half of the endowment. Conversely, participants expected more agentic and conservative but less communal dictators to send less money than less agentic, more liberal, or more communal dictators. Participants also rated unfair dictators as less intelligent but expected less intelligent dictators to send more money. When participants played the Dictator Game with real money, only self-reported communion predicted the money amount sent. Thus, participants' inferences might not reflect reality, but rational social actors should not only fear to appear unfair but also unintelligent.